Estrogen induces distinct patterns of microRNA expression within the mouse uterus() - Nothnick, Warren B. (2010)
Control of estrogenic activity within the uterus is evident as unopposed estrogen action is associated with endometrial pathologies such as endometriosis and endometrial carcinoma. MicroRNAs have emerged as important post-transcriptional regulators which are postulated to fine tune the actions of steroids in many systems including the uterus. The objective of the current study was to examine uterine expression of microRNAs in response to estrogen treatment within the mouse uterus using an ovariectomized, steroid reconstituted mouse model. MicroRNA microarray analysis and subsequent qRT-PCR verification revealed that expression of mirn155, mirn429 and mirn451 was significantly increased by estrogen administration while mirn181b and mirn204 expression was significantly reduced. Pretreatment with the estrogen receptor antagonist ICI 182,780 confirmed that estrogen regulation was mediated via the classical estrogen receptor pathway. This study demonstrates that estrogen regulates specific miRNAs within the murine uterus which may participate in post-transcriptional regulation of estrogen-regulated genes.